Lgr4 Regulates Oviductal Epithelial Secretion Through the WNT Signaling Pathway - Tan, Xue; Zhang, Lingling; Li, Tianqi; Zhan, Jianmin; Qiao, Kun; Wu, Haili; Sun, Shenfei; Huang, Meina; Zhang, Fangxi; Zhang, Meixing; Li, Changwei; Li, Runsheng; et al. (Frontiers in Cell and Developmental Biology, 2021)
The WNT signaling pathway plays a crucial role in oviduct/fallopian development. However, the specific physiological processes regulated by the WNT pathway in the fallopian/oviduct function remain obscure. Benefiting from the Lgr4 knockout mouse model, we report the regulation of oviduct epithelial secretion by LGR4. Specifically, the loss of Lgr4 altered the mouse oviduct size and weight, severely reduced the number of oviductal epithelial cells, and ultimately impaired the epithelial secretion. These alterations were mediated by a failure of CTNNB1 protein accumulation in the oviductal epithelial cytoplasm, the modulation of WNT pathways, and subsequently by a profound change of the gene expression profile of epithelial cells. In addition, selective activation of the WNT pathway triggered the expression of steroidogenic genes, like Cyp11a1 and 3β-Hsd1 through the activation of the transcriptional factor NR5A2 in an oviduct primary cell culture system. As demonstrated, the LGR4 protein modulates a WNT-NR5A2 signaling cascade facilitating epithelial secretory cell maturation and steroidogenesis to safeguard oviduct development and function in mice.